Analisis Arus Kas (Studi Empiris Pada PT. Indosat Tbk) - Risa Ratna Gumilang (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
The cash flow statement is a report that shows the flow of cash or cash that is in the company. The cash statement consists of cash inflows such as proceeds from receipts or sales and cash outflows which consist of expenses such as payment of expenses and expenses. The purpose of this study was to determine the ability of PT. Indosat Tbk. in managing cash flow, especially in determining the projected investment made, based on the cash flow conditions of PT. Indosat Tbk in the period 2016-2018. The results of this study indicate that the comparative analysis of cash flow statements on total cash and cash equivalents, cash flow at the end of the period during the 2016-2018 period shows a percentage of -48.93%, 4.10%, -45.75%, for three consecutive years, and on Trend analysis is at PT. Indosat Tbk. shows the percentage figures of 51.07%, 104.10%, 54.25% for three consecutive years in the 2016-2018 period. Per component analysis shows that cash inflows and outflows are dominated by cash flows from operating activities with a tendency that cash inflows decrease while cash outflows increase. In a special cash flow ratio analysis shows that the cash flow adequacy ratio of PT. Indosat Tbk, shows a figure of 1.57 and a reinvestment ratio which shows a ratio of 25.65% which means that PT. Indosat Tbk is quite good at meeting the company's cash needs.